2018
DOI: 10.1080/21645515.2018.1462427
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of cryptic epitopes in designing a group A streptococcal vaccine

Abstract: A successful vaccine needs to target multiple strains of an organism. Streptococcus pyogenes is an organism that utilizes antigenic strain variation as a successful defence mechanism to circumvent the host immune response. Despite numerous efforts, there is currently no vaccine available for this organism. Here we review and discuss the significant obstacles to vaccine development, with a focus on how cryptic epitopes may provide a strategy to circumvent the obstacles of antigenic variation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 137 publications
1
15
0
Order By: Relevance
“…Most vaccine developments and trials targeted for S. pyogenes are currently focused on the M proteins and their fragments, with the leading ones targeting the N-terminal or the C-repeat region [36]. We have previously shown that peptides in the M protein C-region containing the EEKQISDASRmotif ( Table 1) are potent epitopes for opsonizing antibodies and crucial for the interaction and internalization with monocytic cells; a result corroborated here [4].…”
Section: Discussionsupporting
confidence: 62%
“…Most vaccine developments and trials targeted for S. pyogenes are currently focused on the M proteins and their fragments, with the leading ones targeting the N-terminal or the C-repeat region [36]. We have previously shown that peptides in the M protein C-region containing the EEKQISDASRmotif ( Table 1) are potent epitopes for opsonizing antibodies and crucial for the interaction and internalization with monocytic cells; a result corroborated here [4].…”
Section: Discussionsupporting
confidence: 62%
“…Instead, pathogens may "hide" regions, known as cryptic epitopes, which are normally not very immunogenic but may be protective (30). Targeting cryptic epitopes is of interest for vaccine development against pathogens, such as group A streptococcus, and could be a promising new direction in C. trachomatis vaccine development (32). Together, our present study is of particular interest in the context of vaccine development.…”
Section: Discussionmentioning
confidence: 88%
“…The intensive analysis of 176 emm GAS types [80] has produced a new emm cluster-specific system, which could provide protection to different emm types within the same cluster [75,81]. Five N-terminal M peptides from the E4 emm cluster, containing 17 GAS emm types that are prevalent in the United States, were selected [75].…”
Section: Major Antigen Targets For Gas Vaccinesmentioning
confidence: 99%